The Influence of Internal and External Factors on NPF And NPL - Wahyu Prastowo, Wahyu Prastowo; Hardius Usman, Hardius Usman (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2021)
Indonesia has two types of bank, islamic banking and conventional banking. In their activities, banks are often facing any risks, named financing risk (NPF) in the islamic banking and credit risk (NPL) in the conventional banking. Based on data by OJK, the value of NPF is always higher than NPL. However, in January-August 2020 the NPF tended to decrease while the NPL tended to increase, even indicating a movement that would excited the NPF value. Therefore, it's necessary to the research of the factors that influence both NPF and NPL, including the internal and external conditions of the bank. The data that used as reference is the secondary data from OJK of 10 both islamic and conventional commercial banks from the first quarter of 2019 to the third quarter of 2020. Furthermore, the data is analyzed with panel model fixed effect data analysis with the robust standard error estimation method and panels corrected standard error (PCSE cross-sectional SUR). By using 5% of significance level, this research results that NPF is only significantly and positively influenced by FDR. However, NPL is significantly and negatively affected by the inflation and ROA, also significantly and positively influenced by CAR, LDR, and BOPO.